Current Status of Seaweed Research in the Philippines - Morales, Aames Juriel B. (Animo Repository, 2022)
Seaweeds are large, multicellular marine algae that are ecologically and economically important. In the Philippines, different species are being cultivated and exported as they serve as food or as sources of natural products such as carrageenan. However, the seaweed industry in the country has fallen behind others. Neighboring countries like Indonesia are now leading the global seaweed market. This may be due to factors such as rising abiotic stressors, poor crop management, economic issues, and most especially, a poor research field. Thus, this study utilizes bibliometric analysis to determine the status of the Philippine seaweed research field. A keyword search was done in Scopus to find original English articles published from 2010 to 2021. Out of the initial 1,890 articles found, 122 were relevant and used for further analysis. Heat maps generated from the data revealed that the Philippines produced comparatively less seaweed research relative to fellow Southeast Asian seaweed-producing countries. Sankey diagrams showed that the research produced was also less diverse. Seaweed research was focused on Kappaphycus alvarezii, Eucheuma denticulatum, and ice-ice disease. Furthermore, most Philippine seaweed research articles were published in low-impact foreign journals (SCImago Journal Rank < 1). Therefore, the bibliometric analysis showed that the Philippine seaweed research field is currently in a stale state. This may have contributed to the country’s lagging seaweed industry. Diversity in seaweed research and publication in high-impact journals are encouraged to strengthen the field.